CLINICAL STUDY TO EVALUATE THE EFFICACY OF YAPANA BASTI AND VANARI GUTIKA IN THE MANAGEMENT OF KLAIBYA W.S.R. TO ERECTILE DYSFUNCTION (International Journal of Ayurveda and Pharma Research, 2017)
Successful sexual act is one of the most basic needs for the production of the future generations. Successful sexual act is not possible, if a person is suffering from the Klaibya. Acharya have mentioned different causes of the Klabiya, and Malanashishinta is one among these. Malanshishinta can be compared with the erectile dysfunction on the basis of symptoms. The Sthiradipanchamooladi Yapana Basti (960ml/day for 16days), which is mentioned in the Caraka Samhita for Vajikarana by Caraka and Vanari Gutika (5gm twice daily was given p.o. with milk as Anupana for 30 days) mentioned by Bhavaparkasha in Vajikarana chapter are used in this study. One of the basic aims of this thesis is to evaluate, whether the drugs administered through Basti have any benefit over the drugs administered orally, particularly in reference to the administration of Vajikarana drugs for the treatment. Total 30 patients were selected from the OPD & IPD in the P.G.Department of Panchakarma at National Institute of Ayurveda Jaipur, Rajasthan. The patients were randomly divided into three groups and named as Group A, Group B and Group C, with 10 patients in each group. Highly significant result was found in overall effect the subjective criteria in the group of A, B and group C with 55.55%, 34.78% and 94.44% respectively. In the semen analysis highly significant result was found in group-c with 42.34 % (semen volume), 15.97 % (Sperm count) and in Immotile sperm 45.01% respectively.